Quantitative characterization of geomorphological and topographical features of debris-flow channels at the Alpe di Succiso mountain, Northern Apennines (Italy) - Muhammad Ahsan Rashid; Giovanni Leonelli; Alessandro Chelli (Journal of Maps, 2024)
This study combines the traditional method of geological and geomorphological mapping with a quantitative GIS analysis to examine landforms and debris flows channels. Using a high-resolution DEM (5 m) as a base, the geomorphological map highlights the various landforms around the Alpe di Succiso (Northern Apennines, Italy), including glacial and cryoclastic features, slope landforms and deposits due to gravity (particularly debris flow) and deposits due to running waters. The methodology applied to the channels is based on the geomorphometric parameters derived from the DEM, including Topographic Wetness Index (TWI), Terrain Ruggedness Index (TRI), Slope Angle, and Elevation extracted every 10 m along each channel and grouping the channels in four classes based on their lengths. Within each class, multiple ranking criteria were employed for the identification of channels showing anomalous or common patterns. Debris flow channels exhibit anomalous patterns in the geomorphometric parameters, indicating significant variations in their topographical characteristics..